Comparative Analyses of Vertical Structure of Deep Convective Clouds Retrieved from Satellites and Ground-Based Radars at Naqu over the Tibetan Plateau - Wang, Hui; Guo, Xueliang (Journal of Meteorological Research, 2019)
In order to improve understanding of deep convective clouds over the Tibetan Plateau, characteristics of vertical structure of a deep strong convective cloud over Naqu station and a deep weak convective cloud approximately 100 km to the west of Naqu station, which occurred over 1300–1600 Beijing Time (BT) 9 July 2014 during the Third Tibetan Plateau Atmospheric Science Experiment (TIPEX-III), are analyzed, based on multi-source satellite data from TRMM, CloudSat , and Aqua , and radar data from ground-based vertically pointing radars (C-band frequency-modulated continuous-wave radar and KA-band millimeter wave cloud radar). The results are as follows. (1) The horizontal scales of both the deep strong and deep weak convective clouds were small (10–20 km), and their tops were high [15–16 km above sea level (ASL)]. Across the level of 0°C isotherm in the deep strong convective cloud, the reflectivity increased rapidly, suggesting that the melting process of solid precipitation particles through the 0°C level played an important role. A bright band located at 5.5 km ASL (i.e., 1 km above ground level) appeared during the period of convection weakening. (2) The reflectivity values from TRMM precipitation radar below 11 km were found to be overestimated compared to those derived from the C-band frequency-modulated continuous-wave radar. (3) Deep convective clouds were mainly ice clouds, and there were rich small ice particles above 10 km, while few large ice particles were found below 10 km. The microphysical processes of deep strong and deep weak convective clouds mainly included mixed-phase process and glaciated process, and the mixed-phase process can be divided into two types: one was the rimming process below the level of −25°C (deep strong convective cloud) or −29°C (deep weak convective cloud) and the other was aggregation and deposition process above that level. The latter process was accompanied with fast increase in ice particle effective radius. The above evidence from space-based and ground-based observational data further clarify the characteristics of vertical structure of deep convective clouds over the Tibetan Plateau, and provide a basis for the evaluation of simulation results of deep convective clouds by cloud models.